2009
DOI: 10.5327/z1519-874x2009000300001
|View full text |Cite
|
Sign up to set email alerts
|

Evidência geoquímica de solos formados pela interação de guanos com rochas vulcânicas, Ilha Rata, Fernando de Noronha (PE)

Abstract: RESUMOOs solos fosfáticos encontrados na porção norte da ilha Rata, no Arquipélago de Fernando de Noronha, foram formados pela reação do guano de aves marinhas com as rochas máfi cas intemperizadas da Formação Quixaba. Os minerais fosfáticos determinados no solo incluem a crandalita como o constituinte mais importante. A assinatura do guano preservada no solo é caracterizada por altos teores de Cu, Pb, Zn, As, U, e Sr. Por outro lado, a herança da assinatura geoquímica dos nefelina basaltos é demonstrada pelas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…The transition metals Zn and Ni, found in high concentrations in samples PS and PL (Table 2), confirm the geochemical signatures of guano in the phosphate minerals (Tatur, 1989;Tatur & Keck, 1990;Zdanowski et al, 2005;Liu et al, 2008;Oliveira et al, 2009;Wurster et al, 2015). High content Rb were also detected, which may be another guano geochemical signature, given that the LC/SJ samples are poor in this element.…”
Section: (3)mentioning
confidence: 57%
See 2 more Smart Citations
“…The transition metals Zn and Ni, found in high concentrations in samples PS and PL (Table 2), confirm the geochemical signatures of guano in the phosphate minerals (Tatur, 1989;Tatur & Keck, 1990;Zdanowski et al, 2005;Liu et al, 2008;Oliveira et al, 2009;Wurster et al, 2015). High content Rb were also detected, which may be another guano geochemical signature, given that the LC/SJ samples are poor in this element.…”
Section: (3)mentioning
confidence: 57%
“…High content Rb were also detected, which may be another guano geochemical signature, given that the LC/SJ samples are poor in this element. According to Oliveira et al (2009) andWurster et al (2015), metals are concentrated in bat excrements by bioaccumulation along its food chain either by insects or plants intake.…”
Section: (3)mentioning
confidence: 99%
See 1 more Smart Citation
“…Estudos anteriores levados a efeito numa lagoa situada na mesma ilha de Fernando de Noronha (Oliveira et al, 2009a) (Oliveira et al, 2009b). Por outro lado, estudos que investigaram o comportamento de metais nos mesmos perfi s de solo da ilha de Fernando de Noronha (Oliveira et al, submetido) indicaram a provável contribuição de Hg aerotransportado nos horizontes mais superfi ciais do perfi l MQ.…”
Section: Isótopos De Chumbounclassified
“…Of the existing studies, few report the geochemical evolution of soil formation. Among them, there are the studies of Oliveira et al (2014) that showed the soil phosphatization process of Rata Island (Fernando de Noronha Archipelago) due to the interaction of bird excrement with olivine nephelinites (ankaratritic lavas), and of Oliveira et al (2009) that report high contents of Cu, Pb, Zn, As, U, and Sr in besides soils of this island due to the interaction of guano with mafic rocks, and anomalous concentrations of Ba, Nb, Ta, Cr, Hf, V and Zr due to the geochemical inheritance of local basalts. In the Fernando de Noronha Island, Oliveira et al (2011b) showed that soils developed from mafic rocks (nepheline basalts) presented higher contents of Fe, Co, Ni and Cr, and Oliveira et al (2011a) showed that soils from these rocks concentrate rare earth elements (REEs), preferably the heavy REEs (HREEs).…”
Section: Introductionmentioning
confidence: 99%